Analysis and Modeling of Slotless Permanent Magnet Synchronous Motors (Hungarian Journal of Industry and Chemistry, 2011)
In the automotive industry, where reliability and cost efficiency are especially important, applications based on permanent magnet synchronous motors are gaining more and more ground. The slotless PMSMs have high power and torque density, but they are much more difficult to model than iron cored ones and their sensorless control has not yet been completely solved. The main aims of this study are to better understand the physical phenomena in a slotless PMSM caused by the high frequency injection at standstill, to present an automated measurement environment and measurement results, and to suggest a partial position detection method for slotless PMSMs at standstill.